Fatherlessness in the Social Life of Street Children on Krakatau Ujung Street, Medan Deli District (International Journal of Education and Literature, 2025)
The absence of a father or fatherlessness in a family is a serious problem that affects children's social, psychological, and educational development. This condition becomes even more complex when experienced by street children who live in limited economic conditions and lack family support. The purpose of this study is to reveal the social life of street children on Jalan Krakatau Ujung, Medan Deli District, find the factors that cause fatherlessness, and study the consequences. This study is a qualitative study conducted through a descriptive approach. Data were collected through documentation and in-depth interviews with street children, parents, and community leaders. The results of the study show that the factors causing fatherlessness include divorce, abandonment, and the death of the father. Fathers may also migrate or engage in deviant behavior, such as drug abuse. Children without parents have visible impacts in the form of psychological vulnerability, such as loneliness, lack of self-control, and lack of self-confidence; social impacts, such as difficulty socializing, vulnerability to bullying and exploitation; and educational impacts, such as lack of desire to learn and limited access to education. The lives of street children at the traffic light intersection on Jalan Krakatau Ujung show weak family functioning, especially the role of the father, which encourages children to earn their own living from an early age.